Faktor-Faktor Yang Mempengaruhi Nilai Perusahaan Pada Perusahaan Manufaktur Periode 2016-2018 - Novita Dewi Parlindungan, Merry Susanti (Jurnal Paradigma Akuntansi, 2021)
The purpose of this study is examine growth, capital structure, profitability, firm size and liquidity affect on Firm Value of Manufacturing Companies listed in Indonesia Stock Exchange during 2016-2018. The number of the samples used amount to 53 companies by using purposive sampling method. Panel data were used in this study and analysed using Eviews 9.0. The results of this study are firm growth, capital structure, profitability, firm size and liquidity have no effect on firm value.